الخصائص السيكومترية لمقياس التوجه نحو الحياة لدى طلاب الجامعة ذوي الإعاقة السمعية - عبدالسميع، سعدية عبدالرازق; مفضل، مصطفى أبو المجد سليمان; أحمد، فوزي قابيل همام Ahmed, Fawzi Qabil Hammam (جامعة جنوب الوادي - كلية التربية بقنا, 2024)
يهدف البحث إلى إعداد مقياس التوجه نحو الحياة لدي طلاب الجامعة ذوي الإعاقة السمعية، والتحقق من خصائصه السيكومترية، وتكونت عينة البحث من (۲۰۰) طالبا وطالبة من طلاب الجامعات، حيث تراوحت أعمارهم ما بين (۱۸-۲۵) عاما، بمتوسط حسابي (18.30)، وانحراف معياري (26.46). وقد استخدم البحث مقياس التوجه نحو الحياة لدي طلاب الجامعة ذوي الإعاقة السمعية (إعداد: الباحثة)، كما استخدم الأساليب الإحصائية التالية: التحليل العاملي، معامل ألفا كرونباخ، التجزئة النصفية، معامل الاتساق الداخلي، وقد تكون المقياس من أربعة أبعاد كالتالي: التوجه نحو الرضا بقضاء الله تعالي، التوجه نحو الذات، التوجه نحو المجتمع، التوجه نحو العمل (المهنة)، كما أشارت نتائج البحث إلى أن: مقياس التوجه نحو الحياة لدي طلاب الجامعة ذوي الإعاقة السمعية يتمتع بدرجة مرتفعة من الصدق والثبات، وبالتالي يصلح للاستخدام بدرجة عالية من الثقة. The research aims to prepare a life orientation scale for university students with hearing disabilities, verify its psychometric properties. The research sample consisted of (200) male and female students University, ranging in age from 18 to 25 years, with a mean of (18.30), and a standard deviation of (26.46). The research used the life orientation scale for university students with hearing disabilities (prepared by: the researcher), and the research used the following statistical methods: factor analysis, Cronbach's alpha coefficient, half-division, internal consistency coefficient, and the scale consisted of four dimensions as follows: Orientation towards satisfaction with the judgment of God Almighty, orientation towards self, orientation towards society, orientation towards work (career). The results of the research indicated that: The life orientation scale for university students with hearing disabilities enjoys a high degree of validity and reliability, and therefore is suitable for use with a high degree of confidence.
Keywords: المشكلات النفسية -- ذوي الاحتياجات الخاصة -- الإعاقة السمعية -- طلبة الجامعات